DIVERSITY, DISTRIBUTION AND ABUNDANCE OF SOIL MOLLUSCS IN UiTM NEGERI SEMBILAN FOREST RESERVE - Dayang Nor Shafiqah Awang Shukeran; Nursyazni Abdul Rahim (Journal of Academia)
Soil molluscs have long been used as bioindicators due to their high distribution and functional importance in terrestrial ecosystems. However, their distribution is poorly documented and there is insufficient research about soil molluscs studies. Hence, a study was conducted to establish their current status. The present study aimed to identify the diversity and distribution of soil molluscs in UiTM Negeri Sembilan Forest Reserve. Live snails and dead shells were collected from sixteen 10m x 10m sampling plots of quadrats at three different sites to determine the abundance of this land snail. Sampling was carried out by combining visual observation and sorting-sieving soil and debris samples. The collected samples were preserved in 70% ethanol for later identification in the laboratory. A total of 16 individuals representing six species of three known families were recorded, namely Achatinidae, Ariophantidae, and Camaenidae. Achatinidae had dominated all of three sites with 56% of total samples collected. The statistical analysis showed site A (forest area) had the highest diversity index (H’=1.213) and site B (forest margin) showed the highest evenness index (E=0.982), whereas site C (water tank) had the lowest diversity index (H’=0.562), evenness index (E=0.811) and richness index (R=0.721). One-way ANOVA was also performed on their morphometric variables which resulted in the existence of significant differences on the shell length and width (p<0.05) while weight had no significant differences for all species at all sites (p>0.05). The findings emphasized the importance for long-term studies and further research has to be done in order to gather additional information about the diversity of soil molluscs in this region.